A construção de uma cultura de riscos de desastre em Blumenau, SC: análise da cobertura das enchentes de 2008 e 2011 pelo Jornal de Santa Catarina - Spolaor, Jussara (2012)
Blumenau is a city placed in Médio Vale do Itajaí Santa Catarina, which copes with floods since before its settlement, in the XIX century. Following the city development, problems related to floods and landslides, which are both matters of governmental and communitarian attention appeared. This Master s dissertation focuses on the construction of a disaster risk culture based on governmental and communitarian actions in order to manage these events in Blumenau. We have adopted as our theoretical approach the notion of governamentality (FOCAULT, 1978 [2008]), risk society (BECK, 1986 [2010]) and risk management (SPINK, 2001). In order to understand governmental and communitarian actions during the floods in 2008 and 2011, we have used a local circulation periodic named Jornal de Santa Catarina. The analysis was based on the covers of Jornal de Santa Catarina where we focused on how the media presented the two floods, and on news articles of General and Special editorials of this periodic, where we focused on the construction of a disaster risk culture. On a chronological perspective we focused on the covers used in the first month and on news articles published during the first week after each event. The results suggest a transformation from a disaster culture, guided by the inevitability of the events and action post-disaster, to a disaster risk culture, which praises prevention. They also suggest that the meanings constructed for the characterization of the disaster are defined, overall, by the environmental and human impacts, as well as influences on the city routine. Amongst the official actors, the results suggest an increse in governmental participation between 2008 and 2011, specifically in relation to the City Hall and the Civil Defense. In regards to the local organization, the voluntary intent actions started to be managed by the government in 2011, with little attention given to the point of view of the people directly affected by the disasters (victims) in the two analyzed periods. The results lead us to think that the construction of a disaster risk culture has as focus the management of the hazards by the governmental bodies, which have as object the maintenance of conditions of normalization on the city s routine, including the transition of management from local communitarian actions to the governmental bodies